Distinct neural dynamics in the ventral hippocampus and medial prefrontal cortex during social information processing - Xinnian Wang; Zheng Ma; Yifan Luo; Yechao Han; Chuanzan Zhan; Yulin Ouyang; Yang Zhan (Proceedings of the National Academy of Sciences, 2025)
Social information processing involves coordinated neural activity across distributed brain circuits, with the ventral hippocampus (vHPC) and medial prefrontal cortex (mPFC) playing pivotal roles. However, whether these regions employ distinct coding strategies for different social stimuli remains unclear. Using in vivo electrophysiological recordings in freely interacting mice, we show that although both regions respond to social cues, they engage divergent neural coding mechanisms. During social interaction, the mPFC predominately recruits high gamma oscillations with amplitudes modulated by the phase of theta oscillations, whereas the vHPC primarily depends on low gamma activity phase-locked to theta rhythms. Information-theoretic and machine learning analyses demonstrate that neural populations in the mPFC encode social information more robustly than those in the vHPC. Moreover, integrating spiking activity with local field potential oscillations enhances decoding accuracy compared to spike-only models. Neural manifold analysis showed greater signal-noise angle in the mPFC compared to the vHPC, indicating more discriminative and stable social representations in the mPFC. Our findings demonstrate distinct engagement of neuronal populations and gamma oscillations in the vHPC and mPFC during social information processing.